2022
DOI: 10.1212/wnl.0000000000200015
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Incident Cancer and Guillain-Barré Syndrome Development

Abstract: Background and objectives:Cancer may increase the risk of developing Guillain-Barré syndrome (GBS) due to molecular mimicry or immunosuppression, but the exact relationship is unclear. We aimed to determine the association between incident cancer and the following risk of GBS development.Methods:We conducted a nationwide population-based case-control study of all patients with first-time hospital-diagnosed GBS in Denmark between 1987 and 2016 and 10 age, sex and index date-matched population controls per case.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In accordance with other studies [ 6 ], the most frequent prodromic events were upper respiratory tract infection and gastroenteritis. Guillain–Barré syndrome has also been associated with particular vaccinations [ 25 ], tumor [ 26 ], and autoimmune disease. Other triggers such as trauma and surgery were rarely reported [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with other studies [ 6 ], the most frequent prodromic events were upper respiratory tract infection and gastroenteritis. Guillain–Barré syndrome has also been associated with particular vaccinations [ 25 ], tumor [ 26 ], and autoimmune disease. Other triggers such as trauma and surgery were rarely reported [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous case-reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and small cohort studies, 19,20 as well as the recent case-control study, 3 have reported cancers before, concomitantly with, and shortly after the diagnosis of GBS. These diverse approaches complicate the interpretation of the association, in terms of directionality.…”
Section: Discussionmentioning
confidence: 98%
“… 2 A case-control study showed that cancer can be a risk factor for GBS with the strongest associations for hematological cancer. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first case that reports a patient with ESCC developing GBS. A large case-control study in Denmark found the most common malignancies associated with GBS were lymphoma, lung, and prostate cancers [ 18 ]. Other malignancies that have been associated are nasal SCC, gastric adenocarcinoma, hepatocellular carcinoma, rectal carcinoma, and myelodysplastic syndrome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%